2017
DOI: 10.3389/fimmu.2017.01486
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer Cells from the Subcutaneous Adipose Tissue Underexpress the NKp30 and NKp44 in Obese Persons and Are Less Active against Major Histocompatibility Complex Class I Non-Expressing Neoplastic Cells

Abstract: There are many types of leukocytes reside in subcutaneous adipose tissue (SAT), and among them, natural killer cells (NKs) comprise a major part. We show that the NKs that reside in the SAT (adipose tissue-derived NK cells; ADNKs) of the abdominal region found with phenotypic differences from the NKs circulating in the peripheral blood derived NK cells (PBNKs). In this survey, flow cytometry phenotyping was used to study the differences between the natural cytotoxicity receptor expression on ADNKs and PBNKs of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 47 publications
(49 reference statements)
2
21
0
Order By: Relevance
“…In accordance to previous studies, no significant differences in NKG2D expression were detected within total NK cells between the BMI groups (53,75,(84)(85)(86)(87). In contrast, other studies demonstrated altered NKG2D expression in obese individuals, although with conflicting results.…”
Section: Aside Of This the Expression Of The Activating Counterpartsupporting
confidence: 89%
“…In accordance to previous studies, no significant differences in NKG2D expression were detected within total NK cells between the BMI groups (53,75,(84)(85)(86)(87). In contrast, other studies demonstrated altered NKG2D expression in obese individuals, although with conflicting results.…”
Section: Aside Of This the Expression Of The Activating Counterpartsupporting
confidence: 89%
“…In accordance to the results in mice and rats, obesity was shown to be associated with a decreased NK cell number in blood, liver, uterine, or colon tissue in humans (74,99,(146)(147)(148)(149), whereas several other studies did not observe any differences in the NK cell number comparing normal-weight and obese humans (71,72,84,(150)(151)(152)(153)(154)(155) (Table 4). These discrepancies may be caused by the use of different markers and methods to identify NK cells and subsets in blood and different tissues and individual parameters in the study population, like gender, BMI, ethnicity, and nutritional or metabolic variances.…”
Section: Effects Of Systemic Obesity On Human Nk Cellssupporting
confidence: 84%
“…Investigating the expression of activating NK cell receptors, studies on human subcutaneous adipose tissue NK cells demonstrated that the expression of the NKp30 and NKp44 receptors were decreased in obese subjects, whereas the NKG2D expression levels were not affected by obesity (155). These data indicate a reduced cytolytic activity of NK cells in subcutaneous adipose tissue of obese subjects, which might contribute to the higher susceptibility to infections and increased cancer risk under obese conditions.…”
Section: Tissue-resident Nk Cells In Adipose Tissue Of Obese Individualsmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, O'Rourke and colleagues reported an activated phenotype also for AT resident NK cells that, in obesity, upregulate the NKG2D receptor ( 20 ). Although the total NK cell number is similar in blood and AT of lean and obese subjects, affected or not by CRC, NK cells residing in SAT of obese individuals display a poor cytotoxicity against target tumor cells ( 19 , 28 , 30 ). Moreover, reduced NK cell survival and expansion of IL-10-producing NK cells have been described in other obesity-associated cancers ( 43 ).…”
Section: Innate Lymphocyte Profiles In Obesity and Colorectal Cancermentioning
confidence: 99%